THE ROLE OF YOUTUBE IN POPULAR ESSAY WRITING - Putri Dian Afrinda (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2014)
PERANAN YOUTUBE DALAM MENULIS ESAI POPULERAbstractThis paper discussed the use of YouTube as a media to teach essay writing. It is believed that writing is not an easy feat. The earliest stage in the activity of writing is generating ideas on what to write which can be garnered through reading or listening activities. This is to ensure that the topics to be written are about the latest issues which are able to attract readers’ interest. In this paper, steps to write popular essay by using YouTube broadcasting breaking news are fully elaborated. The use of visual media like YouTube is expected to incite the learners’ creativity. The use of YouTube is based on the fact that people like watching videos regardless to their function as a means of entertainment or source of information. All in all, writing popular essay does not only serve as a media to express ideas but also to change learners’ worldview.Keywords: writing, popular essay, YouTubeAbstrakMakalah ini membahas penggunaan YouTube sebagai media untuk mengajarkan menulis esai. Hal ini diyakini bahwa menulis bukanlah kegiatan yang mudah. Tahap awal dalam kegiatan menulis adalah menghasilkan ide-ide tentang apa yang harus ditulis yang dapat dikumpulkan melalui membaca atau kegiatan menyimak. Hal ini untuk memastikan bahwa topik yang akan ditulis merupakan isu-isu terbaru yang mampu menarik minat pembaca. Dalam tulisan ini, langkah-langkah untuk menulis esai populer dengan menggunakan YouTube akan diuraikan sepenuhnya. Penggunaan media visual seperti YouTube diharapkan dapat menarik kreativitas peserta didik. Penggunaan YouTube didasarkan pada fakta bahwa orang-orang suka menonton video tanpa memperhatikan fungsinya sebagai sarana hiburan atau sumber informasi. Terakhir, menulis esai populer tidak hanya berfungsi sebagai media untuk mengekspresikan ide-ide tetapi juga untuk mengubah pandangan dunia peserta didik.Keywords: writing, popular essay, YouTube